Recent Advances in Blue Perovskite Quantum Dots for Light‐Emitting Diodes. Issue 1 (28th October 2021) - He, Haiyang; Mei, Shiliang; Wen, Zhuoqi; Yang, Dan; Yang, Bobo; Zhang, Wanlu; Xie, Fengxian; Xing, Guichuan; Guo, Ruiqian
Abstract: Metal halide perovskite nanostructures have sparked intense research interest due to their excellent optical properties. In recent years, although the green and red perovskite light‐emitting diodes (PeLEDs) have achieved a significant breakthrough with the external quantum efficiency exceeding 20%, the blue PeLEDs still suffer from inferior performance. Previous reviews about blue PeLEDs focus more on 2D/quasi‐2D or 3D perovskite materials. To develop more stable and efficient blue PeLEDs, a systematic review of blue perovskite quantum dots (PQDs) is urgently demanded to clarify how PQDs evolve. In this review, the recent advances in blue PQDs involving mixed‐halide, quantum‐confined all‐bromide, metal‐doped and lead‐free PQDs as well as their applications in PeLEDs are highlighted. Although several excellent PeLEDs based on these PQDs have been demonstrated, there are still many problems to be solved. A deep insight into the advantages and disadvantages of these four types of blue‐emitting PQDs is provided. Then, their respective potential and issues for blue PeLEDs have been discussed. Finally, the challenges and outlook for efficient and stable blue PeLEDs based on PQDs are addressed. Abstract : In this review, the various strategies for blue perovskite quantum dots (PQDs) based on mixed‐halide PQDs, quantum‐confined all‐bromide PQDs, metal‐doped PQDs, and lead‐free PQDs are focused on. Then, the recent progress of electroluminescence and down‐converted LEDs based on blue PQDs is summarized, which provides valuable guidance to design and create efficient blue LEDs.